Hydrilla Management in Florida Lakes - Stephen F. Enloe; Lyn A. Gettys; James Leary; Ken A. Langeland (EDIS)
Hydrilla (Hydrilla verticillata) is one of the most aggressive submersed invasive plants in Florida waters. It can provide some benefits to fish and wildlife at low levels of coverage, but it also can have major detrimental impacts to water uses, causing substantial economic and environmental hardships. This 7-page fact sheet is a minor revision written by Stephen F. Enloe, Lyn A. Gettys, James Leary, and Ken A. Langeland, and published by the Agronomy Department, November 2019.